Downregulation of long noncoding RNA HCP5/miR-216a-5p/ZEB1 axis inhibits the malignant biological function of laryngeal squamous cell carcinoma cells - Zhang, Sen; Huangfu, Hui; Zhao, Qinli; Li, Yujun; Wu, Lina (Frontiers in Immunology, 2022)
Previous studies found that long non-coding RNA HCP5 regards as oncogene via accelerating cancer cells growth, invasion, metastasis, vascularization, and drug resistance in renal cell carcinoma, gastric cancer, colorectal cancer. Nevertheless, the effect and regulatory mechanism of HCP5 in LSCC remains unknown. In this study, HCP5 expression level was confirmed to be prominently raised in LSCC cell lines. HCP5 knockdown reduced the cell proliferation, migrated ability, and invasive ability of LSCC cell lines. Furthermore, miR-216a-5p was confirmed to sponge by HCP5 and its expression was prominently down-regulated in LSCC cell lines and upregulated in HCP5-silenced LSCC cell lines. miR-216a-5p overexpression down-regulated the cell proliferation, migrated ability, and invasive ability of LSCC cells. Additionally, the protein level of ZEB1, one target gene of miR-216a-5p, was high expressed in LSCC cell lines, and its expression level was downregulated by HCP5 knockdown and miR-216a-5p overexpression. miR-216a-5p inhibitor reversed the effect of HCP5 knockdown. In conclusion, knocking down HCP5 may be a strategy to suppress the malignant biological function of via regulating miR-216a-5p/ZEB1. Therefore, HCP5 may become a prospective therapeutic target for LSCC.